Cooperative Models Practice Type Teams Games Tournaments (TGT) With a Saintific Approach on Material Opportunity - Adimas Eko Permadi; Yus Mochamad Cholily; Alfiani Athma Putri (Department of Mathematics Education University of Muhammadiyah Malang, 2018)
This study aimed to describe learning plan on Opportunity material usingTeams Games Tournaments (TGT) with a scientific approach, and to knowstudent learning activities on learning materials opportunities using TeamsGames Tournaments (TGT) with scientific approach, as well as to know theresults of student learning on learning materials Opportunities using TeamsGames Tournaments (TGT) with scientific approach. Type of this research isdescriptive and the approach used is qualitative and quantitative. Techniqueof collecting data were observation, test, and documentation. The resultsshowed that the planning of TGT learning was only based on 4 components:(1) class presentations, (2) teams, (3) games, and (4) tournaments as well asthe non-implementation of group awards and components combined withscientific approaches, while student learning activities are in type of “good”category since the test results showed that 28 students were complete and 6students were unfinished. In classical, students' completeness reached 82.3%and was said to be complete. These results indicated that learning activitieswith TGT model with scientific approach is good to be applied.